Teaching behavior analysts in an early intensive behavioral intervention setting to conduct a structured mealtime protocol. (13th October 2022) - Ibañez, Vivian F.; Peters, Kerri P.; Bacotti, Janelle K.; Lloveras, Lindsay A.; Van Arsdale, Angela; Vollmer, Timothy R.
Abstract: Children with autism spectrum disorder often display feeding problems, such as consumption of a limited variety of foods. It is also common for these children to be enrolled in early intensive behavioral intervention (EIBI) services for comprehensive treatment. Combined, these factors make it possible that behavior analysts will have a role in a child's clinical care related to feeding. However, given that the etiology of pediatric feeding disorders is complex and multifactorial, clinicians should ensure they have sufficient training and a setting that is appropriate for assessment and treatment. Therefore, we evaluated the effects of behavioral skills training in an EIBI setting to conduct a structured mealtime protocol. Training resulted in increases in procedural integrity, and we replicated these effects for all participants.